Inclusão escolar e a situação do déficit intelectual: metas e conquistas - Carrara, Eliane Fonseca [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This study aims to understand school inclusion, especially in relation to students with Intellectual Deficit (ID) in the scope of elementary education I, and contribute to its improvement. It is understood that the ID imposes a complex and challenging adaptation of the child and the school that receives it, with a view to guarantee the evolution and permanence of these subjects in the school space. It addresses the unique need of each child, anxiety, desire and possible partnerships with the family in the process of school inclusion. We also observe the legislation that protects children with disabilities in relation to their good training and the lack of preparation of teachers, combined with a slow evolution regarding strategies and pedagogical material adopted. The child is not being looked at as the center of the process. In an attempt to place it in the position established by its own legislation, the research analyzes children's testimonies and about them, published by several authors, in addition to highlighting significant aspects analyzed by researchers who are dedicated to the area of school inclusion, searching for new paths for the success of it in its trajectory. This research has a bibliographic character, having as background the experiences lived by the author in the school space during her initial teacher training. It is pointed out as important results of the work the recognition of the possibilities of development of the child with Intellectual Deficit in the school space, whenever the teaching and learning strategies, the interaction with the teacher and / or caregiver, and the pedagogical resources are adequate to their specificities

Este estudo tem como objetivo compreender a inclusão escolar, principalmente no que se refere aos alunos com Déficit Intelectual (DI) no âmbito do ensino fundamental I, e contribuir com seu aprimoramento. Entende-se que o DI impõe uma complexa e desafiante adaptação da criança e da escola que a acolhe, com vistas a garantir a evolução e permanência desses sujeitos no espaço escolar. Aborda-se a necessidade singular de cada criança, a ansiedade, o desejo e as possíveis parcerias com a família no processo de inclusão escolar. Observa-se também a legislação que protege as crianças com deficiência em relação a sua boa formação e o despreparo dos professores, conjugados a uma lenta evolução referente às estratégias e ao material pedagógico adotado. A criança não está sendo olhada como o centro do processo. Na tentativa de colocá-la no lugar estabelecido pela legislação própria, a pesquisa analisa depoimentos de crianças e sobre elas, publicados por vários autores, além de destacar aspectos significativos analisados por pesquisadores que se dedicam à área da inclusão escolar, buscando novos caminhos para o êxito da mesma em sua trajetória.Esta pesquisa tem caráter bibliográfico, tendo como pano de fundo as experiências vividas pela autora no espaço escolar durante sua formação inicial de professora. Aponta-se como resultados importantes do trabalho o reconhecimento das possibilidades de desenvolvimento da criança com Déficit Intelectual no espaço escolar, sempre que as estratégias de ensino e aprendizagem, a interação com o professor e/ou cuidador, e os recursos pedagógicos forem adequados às suas especificidades
Keywords: Educação - Estudo e ensino; Inclusão em educação; Pais e filhos; Ensino - Metodologia; Education - Study and teaching